Context-dependent relationships between multiple sexual pigments and paternal effort. (3rd June 2015) - Grunst, Andrea S.; Grunst, Melissa L.
Lay Summary: Coloration in male birds may indicate paternal ability to females, but colorful males may only be good fathers under certain contexts. In yellow warblers, yellow carotenoid- and red-brown melanin-based pigmentation in combination predict paternal performance. However, more colorful males provide more paternal care only when caring for older, more valuable nestlings, suggesting flexible investment in paternal effort by these males. These data demonstrate that females gain context-dependent paternal benefits by choosing colorful mates. Abstract : Elaborately ornamented males may provide more paternal services than less ornamented males in some contexts but may alternatively invest in territoriality or mating over paternal effort. Two outstanding questions involve whether different types of sexual pigmentation communicate distinct information about paternal strategy and whether highly ornamented males adjust paternal effort to context-dependent benefits. In yellow warblers ( Setophaga petechia ), we explored whether carotenoid- and phaeomelanin-based pigmentation show distinct or complementary relationships to paternal effort and song rate and how males differing in pigmentation adjust behavior to nesting stage, brood size, and territorial challenge. Past studies have suggested that highly melanic male yellow warblers invest in territoriality or mating over paternal effort. However, genetic paternity data from our population indicate that males with high levels of both pigment types retain within-pair paternity but gain little extrapair paternity. Therefore, we predicted that these males should also exhibit higher paternal effort. Highly melanic males sang at high rates during incubation and provisioned incubating females at relatively low rates late in the incubation stage, but showed high late-stage nestling provisioning effort, and did not greatly reduce nestling provisioning rate under territorial challenge. Moreover, as predicted based on genetic paternity data, the relationship between melanin pigmentation and paternal effort varied with the level of carotenoid pigmentation expressed by males, with males expressing high levels of both pigment types provisioning late-stage nestlings at enhanced rates. Thus, the pigment types in combination may signal paternal benefits, and results suggest flexible investment in paternal effort by highly pigmented males.